Tinjauan Yuridis Tindak Pidana Pencabulan Terhadap anak berdasarkan Undang Undang nomor 23 tahun 2002 Tentang Perlindungan Anak (Studi Kasus Perkara Nomor 373/PID/SUS/2015/PN.PBR) - Rendhi Zaka Fahmi; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Today, various kinds of legal issues are increasingly prevalent along with the development ofthe age, science and technology increasingly rapidly. This has resulted in the increasingly complexbehavior patterns of the community. More and more patterns of human behavior are not inaccordance with the norms prevailing in society.These deviant behaviors can lead to an offense and even a crime. Crime is one of the realitiesin life that require special handling. This is because the crime will cause anxiety in the life ofsociety in general.One form of crime that is very disturbing the security and order of public life is a criminaloffense of obscenity. Abetting is an act committed by a person who is motivated by sexual desire todo things that can arouse the passions, which leads to satisfaction in him. The criminal act ofobscenity continues to grow until now. Abuses of helpless people such as children, both men andwomen, are one of the most troubling social problems of society.Criminal acts of intercourse with children are part of morality as regulated in Law Number23 Year 2002 on Child Protection. In the case of a crime of intercourse with a child, it has beenregulated in legislation, which is contained in the Criminal Code (KUHP), which is also containedin the Child Welfare Act as well as in the Juvenile Justice ActLegislation in Indonesia has regulated the formal juridical threat of sanctions granted to theoffender of intercourse namely the Criminal Code Article 287 which formulates; that anyone whohas intercourse with a woman outside marriage, where it is known or should be suspected that sheis not yet fifteen years of age, or if her age is unclear, that it is not yet time to be mated, threatenedwith a maximum imprisonment of nine yearsKeywords: Juridical Review – Criminal Remedy - Child